Real-world outcomes of immunotherapy with or without chemotherapy in first-line treatment of advanced non-small cell lung cancer - Pelicon, Veronika; Cufer, Tanja; Knez, Lea (Frontiers in Oncology, 2023)
Background: Immunotherapy alone (mono-IT) or combined with chemotherapy (chemo-IT) has recently become the cornerstone of first-line treatment for advanced non-small cell lung cancer (NSCLC) patients. Here, real-world outcomes of first-line mono-IT and chemo-IT of advanced NSCLC treated within routine clinical practice at a single academic centre in the Central Eastern European (CEE) region are presented. Materials and methods: A total of 176 consecutive patients with advanced NSCLC treated with mono-IT (118 patients) or chemo-IT (58 patients) were included. At the participating institution, all medical data relevant for providing oncology care are collected prospectively and in a standardized manner using purposely created pro-forms. Adverse events (AEs) were recorded and graded according to Common Terminology Criteria for Adverse Events (CTCAE). The Kaplan‒Meier method was used to estimate median overall survival (mOS) and median duration of treatment (mDOT). Results: The 118 patients in the mono-IT cohort had a median age of 64 years, most were male (59%), 20% had ECOG PS ≥2, and 14% had controlled CNS metastases at baseline. With a median follow-up time (mFU) of 24.1 months, the mOS was 19.4 months (95% CI, 11.1-27.6), and the mDOT was 5.0 months (95% CI, 3.5-6.5). The 1-year OS was 62%. The 58 patients in the chemo-IT cohort had a median age of 64 years, most were male (64%), 9% had ECOG PS ≥2, and 7% had controlled CNS metastases at baseline. With a mFU of 15.5 months, the mOS was 21.3 months (95% CI, 15.9-26.7), and the mDOT was 12.0 months (95% CI, 8.3-15.6). The 1-year OS was 75%. Adverse events of severe grade were recorded in 18% and 26% of patients, and immunotherapy discontinuation due to AEs occurred in 19% and 9% in the mono-IT and chemo-IT groups, respectively. No treatment-related deaths were recorded. Conclusion: The results from the present real-world observational study from a CEE country of first-line mono-IT and chemo-IT in patients with advanced NSCLC suggest similar effectiveness and safety to those observed in randomized clinical trials. However, continuous follow-up will offer better insight into the magnitude of long-term benefits in routine clinical practice.